2020
DOI: 10.3390/ma13153323
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cyclic Loading and Motion on the Implant–Cement Interface and Cement Mantle of PEEK and Cobalt–Chromium Femoral Total Knee Arthroplasty Implants: A Preliminary Study

Abstract: This study investigated the fixation of a cemented PEEK femoral TKA component. PEEK and CoCr implants were subjected to a walking gait cycle for 10 million cycles (MC), 100,000 cycles or 0 cycles (unloaded control). A method was developed to assess the fixation at the cement–implant interface, which exposed the implants to a fluorescent penetrant dye solution. The lateral condyles of the implants were then sectioned and viewed under fluorescence to investigate bonding at the cement–implant interface and cracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…PMMA cement particles have been identified within the joint originating either during the initial implantation procedure [36] or following degradation of the cement mantle particularly if the underlying bone begins to resorb and the stress distribution through the implant or fixation changes [95] . PMMA cement is the most commonly used contaminant in third body wear simulation.…”
Section: Methods For Simulation Of Third Body Wearmentioning
confidence: 99%
“…PMMA cement particles have been identified within the joint originating either during the initial implantation procedure [36] or following degradation of the cement mantle particularly if the underlying bone begins to resorb and the stress distribution through the implant or fixation changes [95] . PMMA cement is the most commonly used contaminant in third body wear simulation.…”
Section: Methods For Simulation Of Third Body Wearmentioning
confidence: 99%
“…A PEEK femoral component would have a modulus closer to bone than cobalt chrome, potentially reducing stress shielding. Stress shielding can contribute to bone resorption and subsequent implant loosening [14][15][16]. Furthermore, the lower weight of a PEEK femoral component would be closer to that of the natural tissue than cobalt chrome and the radiolucency of the PEEK polymer also gives potential for improved imaging of the knee replacement and surrounding tissue in situ [17].…”
Section: Introductionmentioning
confidence: 99%
“…When carrying out pre-clinical wear simulation, especially of novel bearing materials, it is important to understand how different variables influence wear. In this study, the materials of interest were PEEK-OPTIMA™ polymer-on-UHMWPE for use in an all-polymer TKR [14,15,[18][19][20][21] and conventional materials, cobalt chrome-on-UHMWPE. Previous investigations of PEEK-OPTIMA™ polymer-on-UHMWPE in simple geometry wear simulation have shown lubricant temperature to influence wear.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, Lennert de Ruiter et al investigated the initial strength of the PEEK femoral prosthesis bonded to the bone cement and the changes in the bone cement after gait-simulated fatigue experiments. 24,25 They found that although the fixation strength of the PEEK femoral prosthesis with bone cement was lower than that of the metal prosthesis with bone cement, it is adequate for human needs. 24 However, they only studied the initial bond strength of the femoral prosthesis to the bone cement, and did not investigate whether the bond strength of the femoral prosthesis to the bone cement remained reliable after dynamic loading to simulate prolonged human activity.…”
Section: Introductionmentioning
confidence: 99%